High Hydrostatic Pressure Induced Changes in the Physicochemical and Functional Properties of Milk and Dairy Products: A Review - Sergio O. Serna-Hernandez; Zamantha Escobedo-Avellaneda; Rebeca García-García; Magdalena de Jesús Rostro-Alanis; Jorge Welti-Chanes (Foods, 2021)
High-pressure processing (HPP) is a nonthermal technology used for food preservation capable of generating pasteurized milk products. There is much information regarding the inactivation of microorganisms in milk by HPP, and it has been suggested that 600 MPa for 5 min is adequate to reduce the number of log cycles by 5–7, resulting in safe products comparable to traditionally pasteurized ones. However, there are many implications regarding physicochemical and functional properties. This review explores the potential of HPP to preserve milk, focusing on the changes in milk components such as lipids, casein, whey proteins, and minerals, and the impact on their functional and physicochemical properties, including pH, color, turbidity, emulsion stability, rheological behavior, and sensory properties. Additionally, the effects of these changes on the elaboration of dairy products such as cheese, cream, and buttermilk are explored.